Channel Loss Estimation and Test of Ultra-Wideband Propagation from 2 to 10 GHz Application - Lei Gao; Qun Chen (Institute of Advanced Engineering and Science, 2017)
This paper deals with the channel loss models of ultra-wideband radio wave propagation from 2 to 10 GHz application. IEEE 802.15.4a and Okumura channel loss reference models have been introduced and the estimation methods of channel transmission loss have been discussed with the environments of 2 to 10 GHz short range application. The channel transmission loss was measured in ZigBee circuit with 2 kinds of power, using IEEE 802.15.4a and Okumura channel model to estimate the theoretical channel loss, the theoretical value and the actual measured value were compared and analyzed. The analysis shows that the error between the calculated value and the actual measured value of the IEEE 802.15.4a reference model is small in the ultra-wideband ZigBee channel environment, and the error of the Okumura channel loss model is large. The results show that in the environments of 2 to 10 GHz short range application, IEEE 802.15.4a channel loss model is a high precision reference model for the ultra-wideband channel loss calculation.